Adherence to disease modifying therapies in patients with multiple sclerosis - Pileckė , D.; Giedraitienė , N. (Neurologijos seminarai, 2019)
Introduction. Multiple sclerosis is an inflammatory demyelinating disease of the central nervous system. Disease modifying treatment tends to reduce the risk for relapses rate and disease progression, therefore adherence to treatment is essential for outcome. Aim of the study. To examine adherence to disease-modifying therapy in multiple sclerosis patients and identify the factors affecting it. Material and methods. The research was conducted in 2019 at Vilnius University Hospital Santaros Clinics Neurology department using an anonymous questionnaire. Statistical data analysis was performed on IBM SPSS. P value <0.05 was considered statistically significant. Results. Significantly more patients assessed their health as worse if they had the relapse in the last 24 months (p=0.003). Almost half of the patients said they forgot to take at least one dose of medication. Respondents significantly more often forgot to take pills than to inject drugs (p=0.024). Patients who assessed their health better significantly more often forgot to take the medication (p=0.008). Most patients, 78.8% (n=67), acknowledged that their health depended on disease-modifying therapy, though 51.7% (n=44) of respondents were concerned about the side effects that may occur with prolonged use of the drugs. Conclusion. Almost half of the patients forgot at least one dose of medication. Those patients who assessed their health better significantly more often forgot to take the medication. Most respondents relied on the medication prescribed by their physicians and used it responsibly, despite the anxiety about the side effects of long-term medication.